13. Upaya Indonesia dalam Menangani Pemalsuan Obat melalui Member State Mechanism Tahun 2012-2016 - Honesty, Annisa Sholiya; Windiani, Reni; Hanura, Marten (Journal of International Relations, 2017)
The World Health Organization formed an international organization Member StateMechanism which aims to tackle counterfeiting drugs in 2012. Indonesia as one of themember, has always been active in the forum. But in fact, until 2016 Indonesia still fail toaddress drugs counterfeiting. The purpose of this research is to find out why the effortsthat have been made by Indonesia still has not managed to tackle drugs counterfeiting, byusing cualitative method, and explanative tipe of research. The concept of internationalcooperation and the international regime are used to explain the results of the cooperationMember State Mechanism and the role of international regimes WHO in assisting theefforts of Indonesia to address drug counterfeiting.The result from this reseach is there aretwo factors that detain Indonesia in addressing drugs counterfeiting. There is externalfactor that comes from international cooperation and internal factor that comes fromdomestic situation.